BACKSTEPPING CONTROL OF NONLINEAR ROLL MOTION FOR A TRAWLER WITH FIN STABILIZER - Demirel, H.; Dogrul, A.; Sezen, S.; Alarcin, F. (ROYAL INST NAVAL ARCHITECTS, 2017)
A backstepping control design procedure for nonlinear fin roll control of a trawler is presented in this paper. A roll equation consisting of linear and nonlinear damping and restoring moment on the roll response is expressed. Flow analyses are carried out for a scaled model of trawler type fishing vessel including fin stabilizers on both sides of the hull. The fin stabilizer geometry is chosen as NACA 0015 foil section which is widely used in the literature. The flow analyses are performed by using a commercial computational fluid dynamics (CFD) software based on finite volume method. The flow problem is modeled in a 3-dimensional manner while the flow is considered as steady, incompressible and fully turbulent. The numerical model consists of the ship wetted surface and the fin stabilizer in order to investigate the hull-fin interaction. Non-dimensional lift coefficients of the fin stabilizer for different angles of attack are gained. Both controlled and uncontrolled roll motions are examined and simulated in time domain for the maximum lift coefficient. Backstepping controller for roll motion has given a rapid and precise result.
Keywords: Engineering